Kajian Pembentukan Gum Xanthan dari Limbah Padat Sagu oleh Xanthomonas campetris - Palennari, Muhiddin; Rante, Herlina (bionature, 2009)
The purpose of these research was studying of capability for Xanthomonas campetris to bioconversion toward sago solid waste became xanthan gum, to know pH influences and sugar consentration for forming of high xanthan gum. Based on the research was done revealed that X. campetris which doing bioconversion process become xanthan gum which achieved rendemen about 11,026%. Optimum pH to producing of xanthan gum was obtained 7.0. the consentration of sugar for forming the high xanthan gum which 4%. The result of thesereseach is expected to giveÂ  benefit in supporting seeking of the cheap substrate for xanthan gum producing. Keywords : xanthan gum, sago solid waste, Xanthomonas campetris